Dispersal and assimilation of an aquaculture waste subsidy in a low productivity coastal environment. Issue 1 (15th July 2017) - White, C.A.; Nichols, P.D.; Ross, D.J.; Dempster, T.
Abstract: To understand dispersal and assimilation of aquaculture waste subsidies in a naturally low-productivity environment, we applied a novel, rapid transmethylation technique to analyse sediment and biota fatty acid composition. This technique was initially validated at Atlantic salmon farms in Macquarie Harbour, Australia, where sediments were collected at farm and control locations. Subsequently, sediment, benthic polychaete and zooplankton were sampled at sites 0, 50, 250, 500 and 1000 m distant from multiple cages. Results demonstrated an acute deposition zone up to 50 m from cages and a diffuse zone extending 500 m from cages. Changes in sediment concentration of linoleic acid, oleic acid and total fatty acids were effective tracers of farm deposition. Bacterial biomarkers indicated that aquaculture waste stimulates bacterial productivity in sediments, with elevated biomarker concentrations also detected in benthic polychaetes. Overall, fatty acid analysis was a sensitive technique to characterize the benthic footprint of aquaculture influence. Highlights: A transmethylation technique for fatty acid analysis was applied to marine sediments and biota. Fatty acid analysis showed diffuse deposition of aquaculture waste extends 500 m from cages. Changes in sediment concentration of linoleic, oleic and total fatty acids were effective tracers. Bacterial biomarkers suggest aquaculture waste stimulates bacterial productivity in sediments. Elevated bacterial biomarker concentrations were also detected in benthic polychaetes.